INOVASI PELAYANAN “SI JARAN IJO” (JEMPUT BOLA RENTAN ADMINDUK ISO JUJUK OMAH) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BLITAR - Niza Rika Dwi Inka Sari; Meirinawati Meirinawati (Publika, 2022)
The service innovation of Si Jaran Ijo (Pick Ball Vulnerable Adminduk Iso Jujuk Omah) is an innovation created by the Department of Population and Civil Registration (Dispendukcapil) of Blitar Regency to provide convenience for population administration services (Adminduk) especially the recording of Electronic Identity Cards (e-KTP). for people who are included in the category of vulnerable populations, such as neglected, remote, people with mental disorders (ODGJ), people with disabilities, and elderly people. Si Jaran Ijo's innovation is carried out with a ball pick-up system where the Dispendukcapil will immediately deploy a Si Jaran Ijo team to visit the applicant's homes according to the application from the village and sub-district. Si Jaran Ijo's innovation arises because of problems that occur in the field, namely there are still many people in Blitar Regency who do not yet have an e-KTP, one of which is due to the limitations that the community has in accessing population administration services at the Dispendukcapil. The purpose of this study is to describe the service innovation of Si Jaran Ijo in the Dispendukcapil Blitar Regency. The type of research used is descriptive research with a qualitative approach. The focus of his research is using public service innovations according to Bloch (2010), including Product, Process, Organizational, Communication. Data collection techniques through interviews, observation, and also documentation. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. The results of the research on service innovations of Si Jaran Ijo (Pick Ball Vulnerable Adminduk Iso Jujuk Omah), namely: 1) Product, the Dispendukcapil Blitar Regency has produced a product in the form of an e-KTP through the innovation of Si Jaran Ijo. 2) The process, the innovation service of Si Jaran Ijo is carried out with a ball pick-up system, meaning that Si Jaran Ijo officers will visit the applicant's homes to record the e-KTP. 3) The organization, in carrying out Si Jaran Ijo's innovation, the Dispendukcapil of Blitar Regency formed a team of four people to provide services placed in each TLA (Adminduk Service Place) and collaborate with RT, RW and Village to help the success of innovation . 4) Communication, to introduce Si Jaran Ijo's service innovation to the community, the Blitar Regency Dispendukcapil party conducts socialization before the innovation is launched using mass media and also social media. The researcher's suggestions are to add Si Jaran Ijo's operational vehicle in the form of a car so that during the rainy season the implementation of Si Jaran Ijo's innovation can still run smoothly, add officers to the Si Jaran Ijo team so that applicants do not wait too long to get services, and increase socialization related to innovation. Si Jaran Ijo services, one of which can be done by installing a banner.